Analisis Pengaruh Sistem Monitoring Terhadap Kelancaran Pembayaran Kredit Usaha Rakyat (KUR) di Bank Syariah Indonesia KCP Setia Budi - Manurung, Sakinah Halim; Marliyah, Marliyah; Nasution, Muhammad Syukri Albani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of the monitoring system on the smoothness of People's Business Credit (KUR) payments at BSI KCP Setia Budi. Using a quantitative approach with regression analysis using SPSS version 26, the results show a positive relationship and significant influence between the monitoring system and smoothness of KUR payments, with a regression coefficient of 0.518. This finding indicates that an improved monitoring system contributes to smooth debtor payments. A structured monitoring system, supported by digital technology and employee training, allows for regular monitoring of debtor performance, reminders of due dates, and mitigation of the risk of late payments. This study recommends strengthening digitalization and regular evaluation of the monitoring system, as well as further research to explore specific indicators such as evaluation frequency and digital application usage.